An Investigation into the Linguistic Landscape of tourist area in China: A case study of Fulai Mountain tourist area in Shandong Province - Guo, Ying; Ping, Nie; Kunlun, Zhao; Zihan, Qiu; Donglin, Liu; Yudan, Xu; Yu, Wang (Technium Social Sciences Journal, 2022)
Given the current situation that the research on the linguistic landscape in the tourism field is relatively insufficient, we try to carry out an investigation on the construction of linguistic landscape in the Fulai Mountain tourist area of Shandong Province, China, from the perspective of the tourism language landscape in domestic tourist areas. This study found that the language signs in the tourist area are mainly monolingual, supplemented by bilingual and trilingual signs. There are three languages in the Fulai Mountain tourist area: Chinese, English and Korean, among which Chinese is the preferred code, while English and Korean are marginalized in the linguistic landscape. The administrative department of the Fulai Mountain tourist area plays a decisive role in the construction of the linguistic landscape. We also find some problems with the linguistic landscape in the Fulai Mountain tourist area, such as insufficient construction of a diversified linguistic landscape, non-standard translation of language, and lack of design ideas and regional characteristics of the language signs. In the future, tourist area management departments should attach importance to the value of linguistic landscape construction, fully consider tourists’ multi-language needs, improve linguistic landscape design, and regularly carry out linguistic landscape surveys.